PERANCANGAN SISTEM INFORMASI PENGADAAN BARANG PADA STMIK PALCOMTECH PALEMBANG - Atin Triwahyuni; Maria Veronica (Teknomatika, 2013)
STMIK PalComTech Palembang is one of the efforts in the field of education. For a growing company such as PalComTech, as a company engaged in the field of education certainly requires a system of procurement of goods or materials that can provide more accurate information for the company itself which in penginputan procurement data or incoming and outgoing material still use the checkout process into a card or sheet form, for the production of reports is done by way of entering data from the procurement form to a Microsoft Excel form. These companies also often have problems in calculating the amount of the procurement of goods that enter a day, a week, even a month. The methods used in this research is a method of structured systems analysis and design (Structured Systems Analysis And Design). This method is included in the classification of Data Oriented Methodologies that highlight the characteristics of the data to be processed. Generally, the method of structured systems analysis and design based on the resolution of the system elements into modules based on the type of data elements and behavior logic the modules in the system.The system is more effective and efficient in processing data procurement, budgeting and realization so as not to require a long time to do data processing as well as easily in search data and the required report because it has been stored in a database.